Accuracy of Wrist-Worn Heart Rate Monitors: A Comprehensive Review of Smartwatches in Exercise Monitoring - Paluch, Katarzyna; Szypuła, Zofia; Nowak, Aleksandra; Bochenek, Oliwia; Koper, Mateusz; Kałuża, Jessica; Konaszczuk, Adrian; Ratyna, Klaudia; Kozyra, Oliwia; Skarbek, Małgorzata (Quality in Sport, 2024)
Wrist-worn heart rate monitors have become integral in personal health monitoring, particularly during exercise and daily activities. This review evaluates the precision of various commercially available smartwatches in assessing heart rate, focusing on their accuracy across different physical activities, such as walking, running, cycling, and elliptical training. A systematic analysis of 29 peer-reviewed studies, encompassing over 900 participants, was conducted to compare devices like the Apple Watch, Fitbit, Garmin, and others. The results demonstrate significant variation in accuracy depending on the device, type of activity, and individual factors such as body mass index and skin tone. The Apple Watch consistently outperformed other devices, showing the lowest mean absolute percentage error (MAPE), particularly during moderate-intensity activities. In contrast, devices such as the Fitbit Blaze exhibited greater error rates, especially during high-intensity exercises or activities involving significant arm movement. Although wrist-worn heart rate monitors provide users with convenient real-time data, limitations such as motion artifacts, device placement, and external factors may affect their reliability.